Mathematical model of the business process of higher education institutions based on ontological analysis - Honcharenko, Y.; Gorda, O.; Semerikov, S. (Проблеми керування та інформатики, 2025)
Improving the quality of the educational process and bringing it up to modern standards is a complex task that requires a systematic approach and the development of a strategy for improving the quality of service and efficiency. This work examines the specifics of information modeling within an ontological approach to distributed information environments, as well as the essence of ontological analysis of management business processes for the educational process in higher education institutions. An ontological analysis of modeling business processes in higher education institutions and an analysis of the structure, functions, and information flows of organizing and managing educational activities based on a structural approach are conducted. Competence, as an integrated characteristic of the graduate՚s quality, is considered a result of education. Покращення якості освітнього процесу відповідно до сучасних вимог — складне завдання, для виконання якого закладам вищої освіти слід дотримуватися системного підходу та розробляти стратегії підвищення ефективності послуг. Досліджено особливості інформаційного моделювання при онтологічному підході до розподіленого інформаційного середовища. Розглянуто сутність онтологічного аналізу бізнес-процесів керування освітньою діяльністю у закладах вищої освіти та технологію менеджменту для надання якісних освітніх послуг з урахуванням відповідних загальних та спеціальних управлінських компетенцій. Проведено онтологічний аналіз моделювання бізнес-процесів у вищих навчальних закладах.